2010
DOI: 10.1007/s10295-010-0888-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of commercial cellulases and their use in the saccharification of a sugarcane bagasse sample pretreated with dilute sulfuric acid

Abstract: This study aimed to correlate the efficiency of enzymatic hydrolysis of the cellulose contained in a sugarcane bagasse sample pretreated with dilute H(2)SO(4) with the levels of independent variables such as initial content of solids and loadings of enzymes and surfactant (Tween 20), for two cellulolytic commercial preparations. The preparations, designated cellulase I and cellulase II, were characterized regarding the activities of total cellulases, endoglucanase, cellobiohydrolase, cellobiase, β-glucosidase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 43 publications
(46 reference statements)
2
16
1
5
Order By: Relevance
“…Similarly, cellulose conversion range between 27.5 and 47.7% and 15.9 and 48.8% was obtained by employing two enzyme preparations cellulase I and cellulase II, respectively, during 24 h hydrolysis (Santos et al, 2011). Although the hydrolytic efficiency of the biomasses of our study appears to be lower than those reported earlier, it is difficult to make direct comparisons as appropriate enzyme loading and hydrolytic conditions also affect sugars recovery from the substrates (Zhu et al, 2008;Rezende et al, 2011).…”
Section: Enzymatic Saccharification Of the Pretreated Biomassescontrasting
confidence: 54%
“…Similarly, cellulose conversion range between 27.5 and 47.7% and 15.9 and 48.8% was obtained by employing two enzyme preparations cellulase I and cellulase II, respectively, during 24 h hydrolysis (Santos et al, 2011). Although the hydrolytic efficiency of the biomasses of our study appears to be lower than those reported earlier, it is difficult to make direct comparisons as appropriate enzyme loading and hydrolytic conditions also affect sugars recovery from the substrates (Zhu et al, 2008;Rezende et al, 2011).…”
Section: Enzymatic Saccharification Of the Pretreated Biomassescontrasting
confidence: 54%
“…Apresenta grande importância na sacarificação da biomassa, uma vez que a presença de celobiose pode inibir a ação enzimática das endo e exoglucanase (DHILLON et al, 2011;SANTOS et al, 2011). …”
Section: β-Glicosidasesunclassified
“…O teor desses componentes varia bastante entre diferentes amostras de bagaço, como consequência das características genotípicas da cana-de-açúcar, das condições de cultivo, dos métodos de colheita e estocagem do bagaço (HAMES et al, 2003 ESTEVES, 2011;MENDES et al, 2011;SANTOS et al, 2011;SIQUEIRA et al, 2013). Além desses componentes, o bagaço de cana pode conter cinzas, que podem chegar 4,0% da massa total do bagaço, e extrativos, compostos não estruturais, cujos teores podem variar de 4,0 % a 9,0%, dependendo, inclusive, do método analítico utilizado (CANILHA et al, 2011;MILNE et al, 1992;SEABRA et al, 2010;TEMPLETON et al, 2010 WEGENER, 1983a;SAHA, 2003).…”
Section: Parede Celular Da Cana-de-açúcarunclassified
“…Além desses substituintes, grupos acetila e ácidos hidroxicinâmicos (ferúlico e cumárico) também são encontrados (WENDE; FRY, 1997). (LEE et al, 2009;SIQUEIRA et al, 2011SIQUEIRA et al, , 2013 (KANG et al, 2013;SANTOS et al, 2011;TOQUERO;BOLADO, 2014).…”
Section: Parede Celular Da Cana-de-açúcarunclassified
See 1 more Smart Citation